Land Dispute Analysis: Case Study Between Third Parties And Heir In The Decision Of The Supreme Court Of The Republic Of Indonesia Number 629K/Pdt/2023 - Cellia Pambudi, Amanda Devina; Setyo Rini, Fitri; Dyah Palupi, Maya; Atika Zulaeka, Cindy (International Journal of Law and Legal Ethics, 2025)
Inheritance problems often arise due to unfair distribution of assets, not in accordance with the provisions of applicable inheritance laws, both according to Civil Law, Customary Law, and Islamic Law. Inheritance involves the transfer of assets after a person's death to the rightful heirs. In some cases, such as in Supreme Court Decision Number 629K/Pdt/2023, disputes related to inherited land become complex problems, involving various legal aspects and disputed facts. This study analyzes the decision with a normative legal approach, using literature studies on primary, secondary, and tertiary legal materials. The Supreme Court in this decision rejected the cassation application on the grounds of ne bis in idem, emphasizing the importance of the principle of finality in inheritance law. Land disputes, such as those in this case, demonstrate the complexity of inheritance law in Indonesia, especially when involving third parties and decisions that have permanent legal force. The analysis of this decision also includes the obstacles faced in the legal process, including the principle of ne bis in idem, the legal force of previous decisions, and the complexity of proving heir status. This research is expected to contribute to the development of legal science, especially in resolving inheritance land disputes and a deeper understanding of judicial practices in Indonesia.